2017
DOI: 10.1002/2017gl075284
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrometeorological Perspective on the Karakoram Anomaly Using Unique Valley‐Based Synoptic Weather Observations

Abstract: Glaciers in the eastern Hindukush, western Karakoram, and northwestern Himalayan mountain ranges of Northern Pakistan are not responding to global warming in the same manner as their counterparts elsewhere. Their retreat rates are less than the global average, and some are either stable or growing. Various investigations have questioned the role of climatic factors in regard to this anomalous behavior, widely referred to as “The Karakoram Anomaly.” Here, for the first time, we present a hydrometeorological per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 59 publications
5
40
1
Order By: Relevance
“…the "Karakoram anomaly") is consistent with many other studies (Gardelle et al, , 2013Rankl and Braun, 2016). This situation has persisted for at least ∼50 years (Bolch et al, 2017), and has been attributed to increased winter precipitation (Archer and Fowler, 2004) and decreased mean summer temperature (Fowler and Archer, 2006) since the 1960s (Bashir et al, 2017;Forsythe et al, 2017). Glaciers in the Western Kunlun Shan have also been near a balanced state since the 1970s despite an increasing trend in mean summer and annual temperatures (Wang et al, 2018).…”
Section: Introductionsupporting
confidence: 89%
“…the "Karakoram anomaly") is consistent with many other studies (Gardelle et al, , 2013Rankl and Braun, 2016). This situation has persisted for at least ∼50 years (Bolch et al, 2017), and has been attributed to increased winter precipitation (Archer and Fowler, 2004) and decreased mean summer temperature (Fowler and Archer, 2006) since the 1960s (Bashir et al, 2017;Forsythe et al, 2017). Glaciers in the Western Kunlun Shan have also been near a balanced state since the 1970s despite an increasing trend in mean summer and annual temperatures (Wang et al, 2018).…”
Section: Introductionsupporting
confidence: 89%
“…Fowler and Archer () reported a DTR trend of .36, .66 and .08 °C/decade at Gilgit, Skardu and Astore during 1961−1999 on annual basis, respectively. A recent study also reported an increasing regional DTR trend of .31 °C on annual basis (Bashir et al, ). Our study reported a statistically significant increasing DTR trend of .34 °C/decade for whole study area during 1986−2015 also on annual basis.…”
Section: Discussioncontrasting
confidence: 99%
“…This allowed the rate of mass cycling of the glacier to increase even as the mass balance remained neutral. • Bashir et al (2017) found an overall decreasing trend in annual accumulated discharge in the Indus river at Tarbela Dam. According to their study, the annual increase in precipitation and decrease in runoff suggested an overall increase in storage of water in the elevated regions of the watershed, mainly in the form of snow and glaciated ice.…”
Section: Riversmentioning
confidence: 89%